2022
DOI: 10.1001/jamanetworkopen.2021.42093
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes Among African American and Non-Hispanic White Men With Metastatic Castration-Resistant Prostate Cancer With First-Line Abiraterone

Abstract: IMPORTANCEProspective evidence suggests abiraterone is associated with superior progressionfree survival for African American men compared with non-Hispanic White men with metastatic castration-resistant prostate cancer (mCRPC). OBJECTIVE To investigate differences in outcomes with first-line abiraterone therapy betweenAfrican American and non-Hispanic White men with mCRPC in a national real-world cohort. DESIGN, SETTING, AND PARTICIPANTSThis retrospective cohort study used a nationwide electronic health recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 20 publications
3
24
0
Order By: Relevance
“…Interestingly, two studies reported differences in AA outcomes based on race and ethnicity, finding that African American men experienced improved PSA response and OS compared with non-Hispanic White men [ 54 , 55 ]. These findings warrant further analyses of the differential impacts of race and ethnicity on AA versus ENZ outcomes to determine the utility of these patient-specific traits in treatment assignment algorithms.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, two studies reported differences in AA outcomes based on race and ethnicity, finding that African American men experienced improved PSA response and OS compared with non-Hispanic White men [ 54 , 55 ]. These findings warrant further analyses of the differential impacts of race and ethnicity on AA versus ENZ outcomes to determine the utility of these patient-specific traits in treatment assignment algorithms.…”
Section: Discussionmentioning
confidence: 99%
“…cPFS as a composite endpoint has been used previously as one of the endpoints to assess the efficacy of enzalutamide in patients with metastatic PC [28] Another study, which had a median follow-up of 19 months, showed that Black men with mCRPC had a significantly lower risk of death than White men, with a 33% risk reduction when treated with NHTs (either abiraterone or enzalutamide as first-line therapy) [26]. Conversely, a recent study using the community oncology EHR Flatiron Health database with a short median follow-up duration (13 months) showed that although treatment with both NHTs was associated with a similar median OS in White men and Black men (24 months), enzalutamide may have a marked superiority over abiraterone in increasing OS in White men (median OS: 20 months [enzalutamide] vs. 17 months [abiraterone]; HR of death 1.21; 95% CI 1.06-1.38) [27]. The difference in outcomes observed in the latter two studies may be attributable to the inherent strengths and limitations of the study designs and the analyzed data source [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, a recent study using the community oncology EHR Flatiron Health database with a short median follow-up duration (13 months) showed that although treatment with both NHTs was associated with a similar median OS in White men and Black men (24 months), enzalutamide may have a marked superiority over abiraterone in increasing OS in White men (median OS: 20 months [enzalutamide] vs. 17 months [abiraterone]; HR of death 1.21; 95% CI 1.06-1.38) [27]. The difference in outcomes observed in the latter two studies may be attributable to the inherent strengths and limitations of the study designs and the analyzed data source [26,27]. Further, the 12month landmark cPFS analysis was performed in this study to assess early trends in treatment outcome and to address the challenge of non-availability of data for the entire follow-up period due to movement of patients to an oncology setting.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports from VanDAAM (NCT0272373), a multisite validation study of the genomic classifier Decipher in AA men, highlights impact and importance of investing in and including clinical trials focused on minority populations, to reduce disparities in clinical outcomes. 26 Indeed, reports emerging from a retrospective cohort study demonstrated that AA patients with advanced prostate cancer who received first-line abiraterone had significantly longer median survival compared with non-Hispanic White patients (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37) vs. 17 months [IQR: 9−32 months]). 27 A phase III trial showed that AA patients receiving sipuleucel-T had improved overall survival (OS) (30.7 vs. 3.9 months), albeit AA patients made up only 6% of all patients in the study.…”
Section: Bridging the Gap Between Biologic Individual And Macroenviro...mentioning
confidence: 99%
“…26 Indeed, reports emerging from a retrospective cohort study demonstrated that AA patients with advanced prostate cancer who received first-line abiraterone had significantly longer median survival compared with non-Hispanic White patients (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37) vs. 17 months [IQR: 9−32 months]). 27 A phase III trial showed that AA patients receiving sipuleucel-T had improved overall survival (OS) (30.7 vs. 3.9 months), albeit AA patients made up only 6% of all patients in the study. 28 Trust between patients and doctors allows better communication on both sides and better compliance with healthcare recommendations.…”
Section: Bridging the Gap Between Biologic Individual And Macroenviro...mentioning
confidence: 99%